Anti-Parasitic Compounds from Streptomyces sp. Strains Isolated from Mediterranean Sponges - Pimentel-Elardo, Sheila Marie (Molecular Diversity Preservation International, 2010)
Actinomycetes are prolific producers of pharmacologically important compounds accounting for about 70% of the naturally derived antibiotics that are currently in clinical use. In this study, we report on the isolation of Streptomyces sp. strains from Mediterranean sponges, on their secondary metabolite production and on their screening for anti-infective activities. Bioassay-guided isolation and purification yielded three previously known compounds namely, cyclic depsipeptide valinomycin, indolocarbazole alkaloid staurosporine and butenolide. This is the first report of the isolation of valinomycin from a marine source. These compounds exhibited novel anti-parasitic activities specifically against Leishmania major (valinomycin IC(50) < 0.11 μM; staurosporine IC(50) 5.30 μM) and Trypanosoma brucei brucei (valinomycin IC(50) 0.0032 μM; staurosporine IC(50) 0.022 μM; butenolide IC(50) 31.77 μM). These results underscore the potential of marine actinomycetes to produce bioactive compounds as well as the re-evaluation of previously known compounds for novel anti-infective activities.